57 Patient tolerance and the clinical effect of SGLT2 inhibitors in a routine community heart failure population. (6th October 2022) - O'Callaghan, D; Doyle, R; Abboud, J; Barrett, M; Halley, C; McDonald, K
Abstract : Aims: Sodium-glucose Cotransporter-2 (SGLT2) Inhibitors are now advised as standard front line therapy for heart failure reduced ejection fraction (HFrEF) patients irrespective of whether diabetes is present or not. There has now been a multitude of positive trials in favour of SGLT2 inhibitor use with little information on how routine community HFrEF populations respond to this intervention in the setting of already taking maximum tolerated conventional disease modifying therapies. We therefore set out to assess the clinical response (using NYHA and NT-proBNP change) and tolerability of SGLT2 inhibitors in patients attending our outpatient heart failure unit. Methods: All patients commenced on SGLT2 inhibitors as additional medical therapy for HFrEF in a twelve-month period were included in the study. SGLT2 inhibitor therapy was initiated once patients were fully optimised on conventional medical therapy and stable from a heart failure perspective. For all patients commenced on an SGLT2 inhibitor as part of their HFrEF pharmacotherapy we then studied what effect this had on each patients NYHA functional class and NT-proBNP levels before and after initiation of SGLT2 inhibitor. For all patients we recorded whether a not a patient was still taking their SGLT2 inhibitor at most recent follow up appointment at our heart failure unit. Where patients were no longer prescribed SGLT2 inhibitors at follow-up, we analysed the reasons documented for this in the patients electronic patient record. Results: There were 184 patients commenced on SGLT2 in the 12-month period studied of which 78% (144 patients) were male and 26% (48 patients) were diabetic. The average age was 69 years old. Out of the 184 patients, 158 patients (86%) had their initial NYHA class documented in their patient record. The average NYHA functional class at time of commencing SGLT2 inhibitor for these patients was 1.9. At a subsequent follow-up review, 120 patients had a repeat NYHA documented and the average NYHA functional class at this time was 1.7 (with a mean time interval of 4.2months). 86 patients (72%) were in the same NYHA functional class, 28 patients (23%) were now in a lower NYHA functional class whilst 6 patients (5%) were in a higher NYHA functional class. The mean NT-proBNP was 1610pg/mL at initiation of SGLT2 inhibitor and it was 1830pg/mL at the follow-up visit with a mean time interval of 4months. The difference in NT-proBNP's not meeting statistical difference. 166 patients (90%) were still prescribed their SGLT2 inhibitor at most recent follow up. The most common reasons patients had stopped their SGLT2 inhibitors during follow-up was due to urinary tract infections (3% of total patients) and symptomatic hypotension (3% of total patients). Conclusion: For the majority of patients there was no significant change in their reported NYHA class or NT-proBNP levels at follow-up. Overall, we found SGLT2 inhibitors to be a well-tolerated with high adherence rates (90%) at follow up and relatively few side effects warranting discontinuation.